Activated autophagy of innate immune cells during the early stages of major trauma - Chen, Deng; Zhang, Cong; Luo, Jialiu; Deng, Hai; Yang, Jingzhi; Chen, Shunyao; Zhang, Peidong; Dong, Liming; Chang, Teding; Tang, Zhao-hui (Frontiers in Immunology, 2023)
The trauma-induced immune dysfunction has been a major roadblock in achieving better outcomes, which is poorly understood. Autophagy is the crucial catabolic mechanism of immune cells during times of stress but rare study unfolded its immune regulatory effects in the immunologic derangement of trauma patients. In this work, autophagy process and its hub genes were identified in the early stage of major trauma patients according to the whole transcriptome RNA sequencing data obtained from PBMC in cohort of 167 major trauma patients by weighted co-expression network analysis. Single-cell analysis shows that monocytes and neutrophils up-regulated autophagy genes and their antigen presentation enhanced along with the increasing of autophagy genes. In summary, our study generated a trauma-induced immune cell landscape and demonstrated the autophagy is the main functions of innate immune cells and provided insight into the cellular basis of immune dysregulation in major trauma patients.